Performance of State Road Transport Undertakings During Eighth Plan and Estimate for Ninth Plan - Planning Commission (Planning Commission, 1996)
The document analyzes the performance, financial health, and regulatory environment of State Road Transport Undertakings (SRTUs) in India during the Eighth Five Year Plan (1992-97) and provides projections for the Ninth Plan (1997-2002). It highlights improvements in fleet, vehicle, and staff productivity, alongside modest gains in fuel efficiency, while noting persistent financial challenges due to rising input costs and inadequate fare adjustments. The regulatory framework under the Motor Vehicles Act, 1988, addresses fare control, permit management, and coordination with other transport modes. Financial assessments reveal the sensitivity of SRTUs to diesel price fluctuations, with significant losses projected in several states. The study emphasizes strategic policy measures, including fare revisions, private sector participation, tax rationalization, and establishment of depreciation reserves, to ensure sustainable and efficient public transport operations.
Planning Commission Transport Division June, 1996
Planning Commission Transport Division
Keywords: State Road Transport Undertakings; Eighth Plan; Ninth Plan; Fleet Utilization; Vehicle Productivity; Staff Productivity; Financial Performance; Fare Revision; Operational Efficiency; Regulatory Framework; Diesel Price Impact; Transport Policy